PENUNJUKAN ANGGOTA POLRI AKTIF UNTUK MENDUDUKI JABATAN DI LUAR KEPOLISIAN DITINJAU DARI ASAS KEPASTIAN HUKUM - Ronald Limanjaya; Tatang Ruchimat (Jurnal Hukum Adigama, 2020)
The author makes this paper with the title “The Appointment Of Police Officers To Hold Positions Outside The Police Based On The Legal Certainty” because the concern for implementing Indonesia As a Rule of Law. The Rule of law is made to protect the people from government power. The principle of rechtsstaat in Indonesia could be shown by the implementation of separation power between executive, legislative and the judative; protection of human rights, government actions based on law and the others. As the rechtsstaat, one of the most important things is the principle of legal certainty. The legal certainty doesn’t only mean that laws do not contradict each other, the legal certainty also means no difference between law and the implementation itself. From the police law we can clearly see that police are prohibited from occupying any position outside of the police itself. But lately, that police regulation sometimes is violated. In 2018, acting governor of west java was taken from police. One of the police is taken for being a head of the corruption eradication commision. From these cases we can make a conclusion that the phobilited of police to occupy other positions out of police is not implemented properly. This paper is made for finding ways to solve the problem of Legal certainty of this police law problem, to know and understand the legal consequences of an active police position who occupy another position outside the police, and giving preferences for other people who want to research the same problem as this paper.